House of elephants - Ortega, Claribel A. (Ortega, Claribel A. Witchlings (Series), 2024)
Seven and Thorn still have not found a way to cure the hex that turned their friends into stone, magic seems to be working backwards, every new witchling at the Black Moon Ceremony is a spare -- and the Hill Society blames the Spares and wants to prevent them from using magic.